Transposition of Great Arteries with Left Main Coronary Artery Atresia—Case Report - Ahmed F. Elmahrouk; Tamer Hamouda; Mohamed F. Ismail; Ahmed Jamjoom (The Thoracic & Cardiovascular Surgeon Reports, 2018)
Abstract